PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH SERTA DAMPAKNYA TERHADAP LOYALITAS NASABAH (STUDI KASUS PADA BCA BIZZ KCU SEMARANG) - Dewi Setyani, 12.05.51.0010; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2016)
The banking sector in recent years has rapid development. It is caused every kind of banking companies compete to retain customers who already owned, or add new prospective customers. Customer loyalty can be created through a strategy of improving the quality of services, products and increase customer satisfaction by companies to customers. The problem in this research is